Objective physical activity and physical performance in middle-aged and older adults - Spartano, Nicole L.; Lyass, Asya; Larson, Martin G.; Tran, Tuyen; Andersson, Charlotte; Blease, Susan J.; Esliger, Dale W.; Vasan, Ramachandran S.; Murabito, Joanne M. (Experimental gerontology, 2019)
Older adults may have difficulty meeting the Physical Activity (PA) Guidelines. A favorable balance between PA and sedentary time (SED) is an important determinant of physical performance in older adults. Our objective was to explore associations of PA/SED with physical performance across mid-older age in adults without overt mobility disability. Framingham Offspring Study participants free of mobility disability with accelerometry and physical performance data (gait speed, chair stand time, and handgrip strength), were studied in cross-sectional analysis (n = 1352). We regressed physical performance on PA level, measured using steps, moderate to vigorous (MV)PA and SED. We stratified by age groups, adjusted for covariates, and modelled MVPA and SED separately and together as predictors. Only 38% of adults 50–64 years and 15% of adults ≥75 years met the PA Guidelines (i.e., 150 min MVPA per week). Individuals achieving at least 5 min/day of MVPA had 0.062 ± 0.013 m/s greater gait speed and better chair stands and handgrip strength (in women) than those with <5 min/day of MVPA (p < 0.01) across mid-older age. SED was associated with poorer performance on gait speed and chair stand tests, but results were not significant after adjusting for MVPA (p > 0.05). For adults ≥75 years, every 5000 more steps/day related to ~0.045 m/s greater gait speed (p = 0.006). Our cross-sectional study demonstrated that, across mid-older adulthood, MVPA related to better physical performance, but in adults ≥75 years, total steps walked associated with better gait speed. These data warrant future research on the impact of PA on physical performance and health outcomes in older age. •Achieving at least 5 min/day of MVPA related to better physical function.•Accumulating more steps/day related to greater gait speed in adults ≥75 years.•Only 15% of adults ≥75 years met the Physical Activity Guidelines for Americans.